Macroeconomic Accounting and Analysis in Transition Economies - Ouanes, Abdessatar; Thakur, Subhash (Washington, D.C. : International Monetary Fund, 1997)
This book, by Abdessatar Ouanes and Subhash Thakur presents the principal elements of macroeconomic accounting and analysis for the real, fiscal, monetary, and external sectors of a transition economy, using Poland as a case study. Background information, exercises, and issues for discussion are also provided.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet